Evaluation of the effect of implant angulations and impression techniques on implant cast accuracy - An in vitro study - Aman Arora; Viram Upadhyaya; Kirti R Parashar; Divya Malik (Wolters Kluwer Medknow Publications, 2019)
Aim: The purpose of this study was to evaluate the accuracy of implant casts generated with splinted and nonsplinted impression techniques with multiple parallel and nonparallel implants. Materials and Methods: In this experimental study, two edentulous maxillary stainless steel models with seven implant analogs in the central incisor, canine, premolar, and first molar region simulating clinical condition were used (control groups). In one master model, implant analogs were placed parallel to each other, whereas in another model, analogs were placed with a tilt-to-longitudinal axis. Forty stone casts were made from each model using splined and nonsplinted technique using polyether with open-tray technique. Then, the difference in the distance between the master cast and experimental cast in three dimensions was measured by coordinate-measuring machine. One-way ANOVA, post hoc Bonferroni test, and unpaired t-test were used for data analysis. Results: Statistical comparisons were made using ANOVA test, post hoc test, and unpaired t-test. Splinted technique with parallel implants generated interimplant distance values closest to the master model, followed by nonsplinted technique with parallel implants, splinted technique with angulated implants, and nonsplinted technique with angulated implants. Conclusions: Splinted impression technique exhibited higher accuracy than the other technique studies in both parallel and angulated implants.